2020
DOI: 10.1097/ta.0000000000002860
|View full text |Cite
|
Sign up to set email alerts
|

Time to definitive fixation of pelvic and acetabular fractures

Abstract: BACKGROUND The timing of definitive surgical stabilization is a controversial topic of pelvic and acetabular fracture (PAF) management. Historically, staged care with delayed definitive fixation was recommended; however, more recently, some centers have shown early definitive fixation to be feasible in most patients. We hypothesized that time to definitive fixation of PAF decreased without adverse outcomes. METHODS A level 1 trauma center's prospective pelvic fracture d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Across the age spectrum, no association has been demonstrated between time to PA surgery and mortality [ 19 ]. To the best of our knowledge, a recent study by Glogovac et al [ 20 ] is the only paper that investigates the relationship between time to surgery and mortality rates in geriatric patients with acetabular fractures; pelvic fractures were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Across the age spectrum, no association has been demonstrated between time to PA surgery and mortality [ 19 ]. To the best of our knowledge, a recent study by Glogovac et al [ 20 ] is the only paper that investigates the relationship between time to surgery and mortality rates in geriatric patients with acetabular fractures; pelvic fractures were not included.…”
Section: Discussionmentioning
confidence: 99%
“…81 Traditionally, definitive fixation of pelvic fractures was suggested beyond 72 h. However, there is increasing evidence which shows the feasibility of safely performing definitive surgery within this timeframe, which is associated with a very low mortality rate of 2.3%. 82 However, the time-taken for definitive management of these unstable fracture fixations in an acute setting, and their implications have been less studied. Early Appropriate Care (EAC) involves definitive fixation (within 36 h) for unstable fractures of the thoracolumbar spine, pelvis, acetabulum, and/or femur following achievement of definitive thresholds of physiological parameters.…”
Section: Primary Internal Fixation In Pelvic Fractures With Hemodynamic Instabilitymentioning
confidence: 99%
“…Devaney et al revealed in there study based on analysis of 341 patients that between january 2009 and December 2018 time to definitive surgery decreased from 116 to 54 hours without increase of complications and mortality rate [9].…”
Section: Resultsmentioning
confidence: 99%